Trajectory Planning for Reciprocating Motion in Integrated Servo Motor Linear Stages - Max Schnegas; Musa K. Jouaneh (Machines)
Many applications in manufacturing, physical therapy, and machining require linear motion stages to move back and forth at specified rates without exceeding the capabilities of the stages. Growing interest has also been in using integrated servo motors for these applications, which would benefit from the integrated nature of the motor, feedback device, and drive electronics in a single package. This paper introduces a methodology for trajectory planning for the reciprocating motion for a linear motion device. The methodology can be implemented on any device, and a simplified version can be applied to the control software for integrated servo motors. The approach develops motion trajectories, such as triangular or trapezoidal, using a dynamic model of the device and the motor’s torque–speed profile characteristics. The simplified version of the methodology was implemented using an integrated servo motor driving a ball screw stage. Tests were conducted at various motion rates and loads. The experimental results show high accuracy between the predicted and measured motion rates, particularly for rates below three cycles per second. These results suggest that the developed methodology can be a valuable tool for predicting the performance of systems that use integrated servo motors for reciprocating motion applications.